2020
DOI: 10.1109/access.2020.2998697
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Enabled Secure Data Dissemination via Artificial Noise: Joint Trajectory and Communication Optimization

Abstract: This paper studies a single UAV-enabled secure data dissemination system, in which the UAV is employed as an aerial base station to secretly communicate with multiple ground users. To prevent confidential signal intended to scheduled users overhearing by unscheduled ones, artificial noise (AN) is introduced and the UAV transmits a mixture of intended signal and a priori knowledge of AN for scheduled user at each time slot. The trajectory and the AN power splitting factor of UAV as well as the user scheduling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…This has recently gravitated the research community to incorporate the security paradigm for designing UAV communication systems by mainly utilizing the physical layer techniques [32], [33] to avoid extra signaling and overheads incurred by conventional upper-layer cryptography. The information-theoretic secrecy (ITS) for safeguarding UAV communications has been extensively studied by joint design of trajectory and resource allocation in the literature [4], [13], [34]- [38]. However, preventing the content of information message from being deciphered by an eavesdropper for which the ITS aims might be inadequate when the privacy protection matters.…”
Section: Secure and Covert Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has recently gravitated the research community to incorporate the security paradigm for designing UAV communication systems by mainly utilizing the physical layer techniques [32], [33] to avoid extra signaling and overheads incurred by conventional upper-layer cryptography. The information-theoretic secrecy (ITS) for safeguarding UAV communications has been extensively studied by joint design of trajectory and resource allocation in the literature [4], [13], [34]- [38]. However, preventing the content of information message from being deciphered by an eavesdropper for which the ITS aims might be inadequate when the privacy protection matters.…”
Section: Secure and Covert Communicationsmentioning
confidence: 99%
“…In particular, reliable data dissemination is one of the core pillars of an IoT-connected society, wherein the ground wireless access point (AP) typically needs to efficiently transmit information messages to IoT node(s) via multi-hop routing [3]. Such static networking architecture may admit various shortcomings [4]. First, from the perspective of capital and operational expenditures, deploying and operating traditional terrestrial infrastructures in some areas such as mountainous terrain and marine regions can be costly and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…To expose these challenges, a solution based on ANN was suggested that enables UAVs to adaptively exploit the wireless system resources while safeguarding the operation in real-time. In [80], to prevent confidential signals and information from the cyber-attacks and hijacking, an artificial noise (AN) was incorporated. By using the AN with the original signal, the resulting signal is transmitted in a disordered form which makes it difficult for the hacker to decrypt it and extract the original information from it.…”
Section: Wifi Insecurity and Jamming Attackmentioning
confidence: 99%
“…Similarly, there is joint optimization of joint trajectory and user scheduling, considering a UAV security data distribution system that uses unconventional TDMA protocols to transmit confidential information to a legitimate user in each slot. In order to ensure that the information is not stolen by eavesdroppers in the system, another jamming UAV is introduced to interfere with eavesdropping, and the flight trajectory and ground user scheduling of the UAV are jointly optimized within a limited flight cycle to maximize the minimum average safety rate [8] .…”
Section: Joint Optimization Of Trajectory and Uav Communication Resoumentioning
confidence: 99%
“…Due to the need to split a portion of the power to send artificial noise, this will result in the power of sending confidential messages being weakened, because the energy carried by the UAV is very limited, so power allocation is an important issue. The optimal power allocation scheme is often difficult to find, and suboptimal solutions can usually be proposed [12] . However, in the UAV communication scenario, the UAV communication channel is more complicated due to the time-varying nature of the UAV communication network topology.…”
Section: Artificial Noisementioning
confidence: 99%